2022
DOI: 10.3389/fpsyg.2022.886724
|View full text |Cite
|
Sign up to set email alerts
|

Multinational Enterprises’ Knowledge Transfer Received Dimensions and Subsidiary Innovation Performance: The Impact of Human Resource Management Practices and Training and Development Types

Abstract: In this paper, we adopt the resource-based view theory as the theoretical framework to empirically investigate the relationship among knowledge transfer received dimensions (i.e., tacit and explicit), human resource management practices, training and development types (i.e., on-the-job training and development, and off-the-job training and development) and subsidiary innovation performance. Using a survey dataset from 314 subsidiaries of foreign multinational enterprises located in China, we find that: (1) kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…The study utilizes a 7-point scale closed-ended survey questionnaire items ( Boadu et al, 2021b ; Xie et al, 2022a ). We designed our scales in English, translated them to Chinese, and back to English to ensure their reliability ( Brislin, 1970 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study utilizes a 7-point scale closed-ended survey questionnaire items ( Boadu et al, 2021b ; Xie et al, 2022a ). We designed our scales in English, translated them to Chinese, and back to English to ensure their reliability ( Brislin, 1970 ).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we control for financial subsidy, which has the potential to influence GIP. Extant scholarships have proved that it may be linked with enterprise innovative performance ( Boadu et al, 2021a ; Tang et al, 2022 ; Xie et al, 2022a , b ). Enterprises were asked to indicate the financial subsidy that they obtain from authorities.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the past studies by Xie et al [13], Latifi et al [14], and Wang and Wang [15], knowledge transfer and innovation create competitive advantages for the firm, which in turn contribute to better firm performance. Similarly, Ramirez et al [16] and Ferreira et al [17] demonstrated that the intangible assets of a firm (such as innovation capability and intellectual capital) are sources of a firm's competitive advantage and can lead to better performance.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%